Hierarchy of values in the novel "Frozen peaches" by Espido Freire as the reflection of national mentality (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The article deals with a certain hierarchy of the ruling concepts in the novel «Frozen peaches» by Espido Freire as a reflection of values of Spanish society of today. The analysis focuses on a peculiar «women’s» perception of reality, as the problem of the women’s place in Spanish society has always been prevailing in the works of Spanish writers, especially female writers. Changes at all levels of public life, including legislative innovations significantly influenced both a woman’s perception by other women, and her perception of herself that undoubtedly found expression in literary works.
Keywords: feminine values; the hierarchy of values; basic concepts; the Spanish women's prose; conceptual picture of the world